VALLABHBHAI PATEL AND FLAG SATYAGRAHA - Borkar, Gajanan; Khune, Ganesh (International Journal of Research -GRANTHAALAYAH, 2025)
Gandhi was arrested after the suspension of the Non-Cooperation Movement. By this period, one of the leaders who emerged in Gandhi's mind was Vallabhbhai Patel. During Gandhi's imprisonment, he proved the effectiveness of Gandhian thought by opposing the powerful British government on the basis of his philosophy of truth and non-violence through the successful Flag Satyagraha movement. The first commander of this Satyagraha was Jamnalal Bajaj. After his arrest, the Congress executive asked Patel to take the responsibility of this movement. The experiences that Vallabhbhai Patel and other Satyagrahis had in the Nagpur Flag Satyagraha were very exciting and very rare. Future generations will be proud of his heroic story and will get the sacred inspiration of national service and patriotism. In the conduct of Nagpur Satyagraha, Shri Vallabhbhai's management skills, amazing courage, bravery, and extraordinary qualities of keeping people together are seen in the coordination of leadership. The initial soldier is eligible for the high and glorious position of a general in the future. It cannot be guessed today that Patel worked hard for the service of the country under the patronage of Gandhiji. Therefore, it is said that Shri Vallabhbhai was a person of immense courage, discipline, restraint and personality.